Effect of Selenium Supplementation on Lipid Profile: A Systematic Review and Meta-Analysis - Hasani, Motahareh; Djalalinia, Shirin; Sharifi, Farshad; Varmaghani, Mehdi; Zarei, Maryam; Abdar, Mohammad Esmaeili; Asayesh, Hamid; Noroozi, Mehdi; Kasaeian, Amir; Gorabi, Armita Mahdavi; Qorbani, Mostafa (Hormone and Metabolic Research, 2018)
Selenium is an essential mineral that plays a key role in plenty of major metabolic processes. A growing body of literature has shown that selenium deficiency leads to an increase in plasma TC and TG levels. This study explores the effect of selenium supplementation on serum level of lipid profile [total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL), high-density lipoprotein (HDL), very low density lipoprotein (VLDL)]. We systematically searched PubMed/MEDLINE, ISI/WOS, and Scopus (from their commencements to Jan 2016) to identify the papers investigating the association between the intake of selenium and lipid profile. Data extracted from the relevant studies were screened. The pooled standardized mean difference was estimated using the random or fixed effects model. Heterogeneity among the studies was assessed using Q-test. Of the potentially relevant articles screened, 11 articles including 1221 participants were included in this meta-analysis. Results of meta-analysis showed that intake of selenium resulted in a statistically significant improvement in TC, [(SMD): –0.13, 95% CI: (–0.24, –0.02)], TG [(SMD): –0.19, 95% CI: (–0.38, –0.01)] and VLDL [(SMD): –0.34, 95% CI: (–0.63, –0.05)]. The selenium supplementation did not significantly improve lipid profile such as LDL [(SMD): –0.08, 95% CI: (–0.036, 0.19)], HDL [(SMD): 0.01, 95% CI: (–0.164, 0.18)], HDL/TC ratio [(SMD): 0.025, 95% CI: (–0.11, 0.16)], non-HDL-C [(SMD): 0.018, 95% CI: (–0.13, 0.16)]. This meta-analysis suggests that the effect of selenium supplementation on the serum levels of TG and VLDL is marginally significant. However, the supplementation has no effect on other serum lipids. Moreover, the study shows that the effect of selenium supplementation on lipid profile is negative.
Keywords: selenium supplementation; lipid profile; triglyceride; low-density lipoprotein; high-density lipoprotein; total cholesterol